Bromélia ornamental (Neoregelia “fireball”): efeito do Ethrel® e de telas de sombreamento na indução floral e perfilhamento - Pereira, Jéssica Soares (2016)
Edaphoclimatic aspects as the amount of solar radiation and the use of flowering inducers are determining factors in the external characteristics of bromeliads and flowering of several botanic species. Therefore, the aim of this study was to evaluate the combined effects of light restriction, from the use of shade screens, associated with the application of five doses of the commercial product Ethrel® in inducing flowering of bromeliad Neoregelia "fireball". This work was conducted from March to July 2015 in a protected environment with black screens in three different densities of shading (30, 50 and 70%). The plants were distributed in the three greenhouse in the randomized block design, arranged in a split-plot, where the plots was shadow factor and the subplots was used the dose factor. The doses of Ethrel® applied were: D0 (no Ethrel®), D1 (2 ml / L -1), D2 (3 ml / L-1), D3 (4 mL / L-1), D4 (8 mL / L -1), and D5 (16 ml / L-1), diluted in 1 L of distilled water, which was applied to 10 ml of the solution in the center of the rosette plant. The count of flowering were performed weekly form from the first flowering of evidence. The number of shoots was observed at 30 and 60 days after flowering (complete opening of the first flower). The other morphological and physiological variables were measured after the plants reach the third floral development stage (110 days after implantation of the experiment).The use of different levels of shading influence at the height of this species, the RAF and the presence of higher rates of Chla, Chlb and anthocyanin content of bromeliads. The inflorescence development stages were influenced by doses of Ethrel® used where the dose 4 ml.l-1 gave the presence of 100% of flowering plants in shade screen of 30% and 70%. The dose of 8 ml L-1 of Ethrel® was less efficient in inducing flowers for this species. The number shoots produced was influenced by doses of Ethrel®. The plants in the shade screen of 70% had relations gas exchange and significantly higher photosynthesis. The Ethrel® enables the production of bromeliads, inducing flowering and induce shooting faster and more efficiently.